Unusual ligand assistance in molecular electrocatalysis via interfacial proton charge assembly - Mukhopadhyay, Sanchayita; Kottaichamy, Alagar Raja; Chame, Pallavi Vyankuram; Ghosh, Prasenjit; Vinod, Chathakudath Prabhakaran; Makri Nimbegondi Kotresh, Harish; Kanade, Sandeep C.; Thotiyl, Musthafa Ottakam (Journal of Physical Chemistry Letters, 2023)
We show that the ability of the ligand to reorganizethe electricdouble layer (EDL) often dominates the electrocatalysis contrary totheir inductive effect in the spectrochemical series, leading to counterintuitiveelectrocatalysis. With water oxidation and chlorine evolution as theprobe reactions, the same catalytic entity with carboxy functionalizedligand exhibited surprisingly higher electrochemical activity in comparisonto the aggressively electron-withdrawing nitro functionalized ligands,which is contrary to their actual location in the spectrochemicalseries. Spectroscopic and electrochemical analyses suggest the enrichmentof catalytically active species in the carboxy substituted ligandvia proton charge assembly in the EDL that in turn enhances the kineticsof the overall electrochemical process. This demonstration of lessobvious ligands becoming indispensable in electrocatalysis suggestsa blind designing of ligands solely based on their inductive effectshould be reconsidered as it will prevent the utilization of the maximumpotential of the molecule in electrocatalysis.